Good names beget favors: The impact of country image on trade flows and welfare - CHANG, Pao-Li (Institutional Knowledge at Singapore Management University, 2022)
This paper estimates the effects of time-varying consumer preference bias on trade flows and welfare. We use a unique data set from the BBC World Service Poll, which surveys (annually during 2005–2017 with some gaps) the populations of a wide array of countries on their views of whether an evaluated country is having a mainly positive or negative influence in the world. We identify the effects on consumer preference parameters due to shifts in these country image perceptions and quantify their general equilibrium effects on bilateral exports and welfare (each time for an evaluated exporting country, holding the exporting country’s own preference parameters constant). We consider five important shifts in country image: the George W. Bush effect, the Donald Trump effect, the Senkaku Islands Dispute effect, the Brexit effect, and the Good-Boy Canadian effect. We find that such changes in bilateral country image perceptions have quantitatively important trade and welfare effects. The negative impact of Donald Trump’s “America First” campaign rhetoric on the U.S.’s country image might have cost the United States 4%–5% of its total exports and welfare gains from trade. In contrast, the consistent improvement of Canada’s country image between 2010 and 2017 has amounted to more than 8% of its total welfare gains from trade.